2003
DOI: 10.1038/nature01835
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of auditory spatial acuity from neural images on the owl's auditory space map

Abstract: The owl can discriminate changes in the location of sound sources as small as 3 degrees and can aim its head to within 2 degrees of a source. A typical neuron in its midbrain space map has a spatial receptive field that spans 40 degrees--a width that is many times the behavioural threshold. Here we have quantitatively examined the relationship between neuronal activity and perceptual acuity in the auditory space map in the barn owl midbrain. By analysing changes in firing rate resulting from small changes of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 28 publications
5
76
0
Order By: Relevance
“…A further possible complication of level in bilateral cochlear implants is hypersynchronization to amplitude modulation for high carrier pulse rates (Litvak et al 2001;. Processing of ITDs is typically done by neurons that are broadly-tuned to ITDs using a population code, rather than by narrowly tuned elements (Fitzpatrick et al 1997;McAlpine et al 2001;Bala et al 2003). Decreasing the range of ITDs over which neurons can show a graded response could disrupt the operation of this population code.…”
Section: Effects Of Sound Intensitymentioning
confidence: 99%
“…A further possible complication of level in bilateral cochlear implants is hypersynchronization to amplitude modulation for high carrier pulse rates (Litvak et al 2001;. Processing of ITDs is typically done by neurons that are broadly-tuned to ITDs using a population code, rather than by narrowly tuned elements (Fitzpatrick et al 1997;McAlpine et al 2001;Bala et al 2003). Decreasing the range of ITDs over which neurons can show a graded response could disrupt the operation of this population code.…”
Section: Effects Of Sound Intensitymentioning
confidence: 99%
“…However, there is a possible neural explanation for the increase in threshold when the physiological range is exceeded, at least in rabbits. At the peaks of the ITD curves the response variability is greater and the change to a small change in ITD is less than on the steepest slope (also see Bala et al, 2003;Shackleton et al, 2003). Most neural tuning curves in the rabbit show a peak in the range of 100-300 μs (Kuwada et al, 1987).…”
Section: Comparison With Neural Thresholdsmentioning
confidence: 99%
“…The surgical procedures for the physiological experiments on owls have been described in detail previously and the data analyzed here have also been analyzed in previous work (Keller and Takahashi, 2000;Bala et al, 2003). Briefly, adult barn owls were anesthetized by intramuscular injections of ketamine (0.05-0.1 ml/h; 100 mg/ml) and diazepam (0.025-0.05 ml/h; 5 mg/ml) and given a prophylactic dosage of ampicillin (0.2 ml, i.m.…”
Section: Physiological Experimentsmentioning
confidence: 99%
“…As a basis for comparison with the gerbil, we also analyzed responses to noise bursts at different ITDs from the exterior nucleus of the ICx in anesthetized barn owls (n ϭ 58 with significant ITD tuning). While there are many important anatomical and physiological differences between the central nucleus of the mammalian IC and the avian ICx, the barn owl ICx responses, in which the representation of ITDs is known to be sparsely distributed across the population (Knudsen and Konishi, 1978;Bala et al, 2003), provide a clear example with which to compare the gerbil responses. The ability of barn owls to localize sounds in the azimuthal plane has been well studied , and it has been shown that this ability relies almost exclusively on sensitivity to ITDs (Poganiatz et al, 2001).…”
Section: Decoding Gerbil and Barn Owl Population Responses To A Hypotmentioning
confidence: 99%